Rekonstruksi Teologi Islam: Studi Analisis Pemikiran Hassan Hanafi - Negara, Muhammad Adress Prawira (Ma'had Aly Idrisiyyah, 2023)
One of the Islamic goals taught by Prophet Muhammad SAW was liberation. However, after the death of Prophet SAW and his companions, this mission was no longer felt by Muslims. Hasan Hanafi explained that classical Islamic theology is unable to encourage Muslims to be aware of the suffering they are experiencing. In fact, the discourses contained in theology are only used to reinforce theocentric teachings rather than talk about human problems. Hassan Hanafi said that Islamic theology is not only concerned with theocentric issues and other metaphysical matters, but Islamic theology also deals with issues of belief, action, and social systems. This study aims to examine in depth the concept of liberation theology initiated by Hassan Hanafi. This research uses qualitative methods with the type of literature. This research uses qualitative methods with the type of literature. This research is a descriptive analysis that explains and describes the object of study and is analyzed in depth. The results of this study The renewal in this theology did not result in the loss of classical cultures, but this renewal was very instrumental in countering all threats that came to Muslims. This kind of renewal aims to eliminate all forms of oppression and give birth to an independent, progressive, egalitarian, and unitary Islamic society.